Cleaning of concentrated wastewater production of lemonic acid - Zaharova, Ruslana; Bublienko, Natalia; Semenova, Olena (My University, 2020)
The description of water consumption in the production of citric acid. The main indicators of wastewater are described and the use of methane fermentation is recommended for their purification. Studies have shown the possibility of obtaining a significant amount of biogas (9 dm3/ dm3), which is characterized by high methane content (up to 80 %).
Keywords: wastewater; citric acid production; biochemical purification; methane fermentation; стічні води; виробництво лимонної кислоти; біохімічне очищення; метанове бродіння; кафедра екології та екоменеджменту